(untitled) (Journal of Hama University, 2024)
This experiment is done on (25) awassi ewes, through the period from 7/2021 to 7/2023. divided into three categories: AA, AG, GG according to their genotype of growth hormone by analysis on PCR using the Haeiii cutting enzyme. The study was conducted on some production characteristics ( daily and total milk production, lactation period, the percentage of fat and protein in the milk and the type of pregnancy (twin, single) lamb. The AG group was significantly superior in terms of the prevalence of the genotype, the group GG was gave higher results in daily and total milk production and the lactation period for 0.85 kg, 69.1kg, 79.7 days respectively but there were no significant differences at the level p≤0.05. The results show a superiority in the percentage of fat and protein in milk for the AG genotype over the other groups, reaching 5.82 and 4.41, respectively. Although there are differences, they do not reach the level of significance. While the group AG significantly outperformed the group AA in the percentage of cheese coefficient . Group AA outperformed the rest of all groups in the rate of twin pregnancies.